Effectiveness and safety of rapid clozapine titration in schizophrenia. (20th December 2013) - Ifteni, P.; Nielsen, J.; Burtea, V.; Correll, C. U.; Kane, J. M.; Manu, P.
<x xml:space="preserve">Abstract</x> Objective Clinical guidelines recommend slow clozapine dose titration in order to decrease the risk of seizures and hypotension. The recommendation may delay adequate control of severe psychotic symptoms. We evaluated the safety and effectiveness of rapid clozapine titration in patients who had been previously exposed to the drug and in patients who received clozapine for the first time after failing to respond to other antipsychotics. Method Analysis of hospital course of a consecutive cohort of schizophrenia patients (N = 111) who received 25–100 mg of clozapine as needed every 6 h the first treatment day, followed by upward adjustments of 25–100 mg/day. Results Symptom control was obtained with an average dose of 353 ± 174 mg/day after 4.1 ± 3.1 days in the 73 patients previously treated with clozapine. For the 38 patients initially started on other antipsychotics, the average clozapine dose required for symptom control (409 ± 188 mg/day) was reached after 7.1 ± 4.8 days. None of the patients had seizures, severe hypotension or other major adverse reactions. Conclusion In this naturalistic cohort study rapid clozapine titration appeared safe and effective for the treatment of schizophrenia. The results justify controlled clinical trials of this treatment method.